Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1186/s12938-015-0072-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual identification via electrocardiogram analysis

Abstract: BackgroundDuring last decade the use of ECG recordings in biometric recognition studies has increased. ECG characteristics made it suitable for subject identification: it is unique, present in all living individuals, and hard to forge. However, in spite of the great number of approaches found in literature, no agreement exists on the most appropriate methodology. This study aimed at providing a survey of the techniques used so far in ECG-based human identification. Specifically, a pattern recognition perspecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 122 publications
(118 reference statements)
2
70
0
11
Order By: Relevance
“…(2) Collectability, that is an ECG signal can be easily measured compared to other biological signals [6]. (3) Uniqueness, which implies that an ECG signal is unique (4) Permanence, which means it is permanent and finally (5) Performance, which is similar to biometric system, it is secure, efficient and accurate [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Collectability, that is an ECG signal can be easily measured compared to other biological signals [6]. (3) Uniqueness, which implies that an ECG signal is unique (4) Permanence, which means it is permanent and finally (5) Performance, which is similar to biometric system, it is secure, efficient and accurate [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The normalized amplitude is relevant since it provides information on the ability to analyze the morphology of each wave for clinical diagnosis. Parameters related to normalized amplitudes (or amplitude ratios) of the cardiac waves have been extensively used in the literature for different aims, ranging from biometric recognition systems to developing new diagnostic algorithms [28,29]. In the present work, peak-to-peak amplitudes of P and T waves were normalized to those of the whole average beat, that is, QRS in almost all cases.…”
Section: Ecg Analysismentioning
confidence: 99%
“…In [27,28], the authors showed how IPI-based values can be employed as cryptographic keys. In addition, ECG biometrics is a growing field in which some approaches are based on characteristics’ points (including R-peaks and IPIs) [29,30]. …”
Section: Motivation and Related Workmentioning
confidence: 99%